Mechanically robust bamboo node and its hierarchically fibrous structural design. Issue 2 (22nd September 2022) - Chen, Si-Ming; Zhang, Si-Chao; Gao, Huai-Ling; Wang, Quan; Zhou, LiChuan; Zhao, Hao-Yu; Li, Xin-Yu; Gong, Ming; Pan, Xiao-Feng; Cui, Chen; Wang, Ze-Yu; Zhang, YongLiang; et al.
ABSTRACT: Although short bamboo nodes function in mechanical support and fluid exchange for bamboo survival, their structures are not fully understood compared to unidirectional fibrous internodes. Here, we identify the spatial heterostructure of the bamboo node via multiscale imaging strategies and investigate its mechanical properties by multimodal mechanical tests. We find three kinds of hierarchical fiber reinforcement schemes that originate from the bamboo node, including spatially tightened interlocking, triaxial interconnected scaffolding and isotropic intertwining. These reinforcement schemes, built on porous vascular bundles, microfibers and more-refined twist-aligned nanofibers, govern the structural stability of the bamboo via hierarchical toughening. In addition, the spatial liquid transport associated with these multiscale fibers within the bamboo node is experimentally verified, which gives perceptible evidence for life-indispensable multidirectional fluid exchange. The functional integration of mechanical reinforcement and liquid transport reflects the fact that the bamboo node has opted for elaborate structural optimization rather than ingredient richness. This study will advance our understanding of biological materials and provide insight into the design of fiber-reinforced structures and biomass utilization. Abstract : Mechanical reinforcement schemes and underlying mechanisms within the sophisticated multiscale fibrous structure of one bamboo node have been discovered, providing insight into engineering structural material design and biomass utilization.